Impact of COVID-19 on birth rate trends in the Italian Metropolitan Cities of Milan, Genoa and Turin. (September 2021) - De Rose, A.F.; Ambrosini, F.; Mantica, G.; Terrone, C.
Abstract: Objectives: The COVID-19 pandemic has led to major changes in the lives of people worldwide, including changes in personal and social habits. Faced with this global health emergency, governments have imposed strict mitigation measures. Within this context, and considering data from previous epidemics, it has been proposed that birth rates may have been negatively impacted. This study aimed to assess the trends in birth rates in three main industrial cities in Northern Italy during the COVID-19 pandemic. Study design: This was a retrospective and observational study. Methods: Data on birth rates were collected and compared for the cities of Milan, Genoa and Turin from November 2019 to January 2020 (i.e. before the COVID-19 pandemic) and during the same period of the following year (i.e. during the COVID-19 pandemic). Results: Birth rates in the cities of Milan, Genoa and Turin decreased by 55%, 12% and 33%, respectively. Conclusions: The decrease in birth rates during the COVID-19 pandemic in these three industrialised cities is in line with the demographic effects of previous pandemics. The negative impact of COVID-19 on conception may be a result of various underlying factors. Further studies are required to verify how social and demographic factors may influence birth rates during pandemics.